Definition, aims, and implementation of GA2LEN Urticaria Centers of Reference and Excellence. Issue 8 (30th May 2016) - Maurer, M.; Metz, M.; Bindslev‐Jensen, C.; Bousquet, J.; Canonica, G. W.; Church, M. K.; Godse, K. V.; Grattan, C. E.; Hide, M.; Kocatürk, E.; Magerl, M.; Makris, M.; et al.
Abstract: Background: GA²LEN, the Global Allergy and Asthma European Network, has recently launched a program for the development, interaction, and accreditation of centers of reference and excellence in special areas of allergy embedded in its overall quality management of allergy centers of excellence. The first area chosen is urticaria. Urticaria is a common and debilitating condition and can be a challenge for both patients and treating physicians, especially when chronic. Centers of reference and excellence in urticaria (UCAREs) can help to improve the management of hard‐to‐treat conditions such as urticaria. Aims: Here, we describe the aims, the requirements and deliverables, the application process, and the audit and accreditation protocol for GA²LEN UCAREs. Results: The main aims of GA²LEN UCAREs are to provide excellence in urticaria management, to increase the knowledge of urticaria by research and education, and to promote the awareness of urticaria by advocacy activities. To become a certified GA²LEN UCARE, urticaria centers have to apply and fulfill 32 requirements, defined by specific deliverables that are assessed during an audit visit. Discussion and Conclusion: The GA²LEN UCARE program will result in a strong network of urticaria specialists, promote urticaria research, and harmonize and improve urticaria management globally.